2003
DOI: 10.1242/jeb.00232
|View full text |Cite
|
Sign up to set email alerts
|

High mechanical efficiency of the cross-bridge powerstroke in skeletal muscle

Abstract: SUMMARY We were interested to estimate the maximum mechanical efficiency with which chemical energy derived from ATP hydrolysis is converted into mechanical work by individual cross-bridges when they perform their powerstroke synchronously. Glycerinated rabbit psoas muscle fibres, containing ATP molecules almost equal in number to the cross-bridges within the fibre, were activated to shorten under various afterloads by laser-flash photolysis of caged Ca2+. In these conditions, almost all the cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…Documenting the efficiency of individual myosin motors in the lattice is challenging since, by operating asynchronously, they perform work on negatively strained neighbors (83). To estimate myosin motor efficiency, Sugi et al (182) recorded the power generated by glycerinated fibers when cross-bridge powerstrokes were synchronized by limiting the amount of ATP in the system to approximately one per myosin motor and using the laser-induced release of caged calcium for activation. Their study showed that the efficiency of individual myosin motors within the filament lattice is, conservatively, 70% (182), which is much greater than previous estimates in vertebrate muscle.…”
Section: Efficiency Is An Emergent Property Of Multiscale Interactionsmentioning
confidence: 99%
“…Documenting the efficiency of individual myosin motors in the lattice is challenging since, by operating asynchronously, they perform work on negatively strained neighbors (83). To estimate myosin motor efficiency, Sugi et al (182) recorded the power generated by glycerinated fibers when cross-bridge powerstrokes were synchronized by limiting the amount of ATP in the system to approximately one per myosin motor and using the laser-induced release of caged calcium for activation. Their study showed that the efficiency of individual myosin motors within the filament lattice is, conservatively, 70% (182), which is much greater than previous estimates in vertebrate muscle.…”
Section: Efficiency Is An Emergent Property Of Multiscale Interactionsmentioning
confidence: 99%